The future isn’t what it used to be: A systemic perspective to knowledge-building - Zamana, Felipe (Farol, 2024)
This article examines the creative process of knowledge-building through a systemic point of view. First, we will explore ancient human practices to highlight the importance of flexible structures with circumstantial roles in social and intellectual development. Then, we address how industrial practices influenced business, education, and professional development, fostering individualism. Finally, we discuss how the creative ecosystem concept can aid us in understanding our context and facing societal challenges more effectively in the future.
Keywords: Knowledge; Productivity; Creativity; Creative Ecosystems